PENGARUH PEMATAHAN DORMANSI SECARA FISIK DAN KIMIA TERHADAP KEMAMPUAN BERKECAMBAH BENIH MUCUNA (Mucuna bracteata D.C) - Retno Puji Astari; Rosmayati Rosmayati; Eva Sartini (Universitas Sumatera Utara, 2014)
Generative propagation of mucuna produces low germination percentage and requires long time togerminate due to seed dormancy which is caused by the seed coat that is impermiable to oxygenand/or water. This study is aimed to find out the effect of the treatment of chemical compund ondormancy realease of mucuna seed. This study was held in the Laboratory of Plant BreedingAssociation at Agriculture Faculty of University of North Sumatera (USU) (± 25 m asl) from Mayto June 2013 by using random block design with 8 treatments. Each treatment was replicated 3times. The treatments were without treatment (A1), the seed coat scarification and soaking in waterfor 30 minutes (A2), soaking in 1% of H2SO4 for 10 minutes (A3), soaking in 1% of H2SO4 for 15minutes (A4), soaking in 1% of KNO3 for 12 h ours (A5), soaking in 1% of KNO3 for 24 hours(A6), soaking in 300ppm of GA3 for 3 hours (A7), and soaking in 300ppm of GA3 for 5 hours(A8). The parameters were moisture (%), germination capacity (%), germination speed (% / etmal),dormancy intensity (%). The results show that dormancy release has significant effect on moisture(%), germination capacity (%), germination speed (%/etmmal), and dormancy intensity (%). Thetreatment of soaking in 1% of H2SO4 for 10 minutes (A3), soaking in 1% of KNO3 for 24 hours(A6), and soaking in 300 ppm of GA3 for 5 hours (A8) were the treaments that were able to releaseMucuna seed dormancy with germination capacity >80%; treatments A3 and A6 each produces91.67% and A8 produces 86.67%. The best dormancy release was produced by treatment A6 that issoaking in 1% of KNO3 for 24 hours compared with H2SO4 and GA3.Keywords: Mucuna, dormancy, dormancy breaking